Color Sensors in Smart Food Packaging - Roman V. Kryuk; Marina G. Kurbanova; Anastasia Yu. Kolbina; Konstantin B. Plotnikov; Igor B. Plotnikov; Andrey N. Petrov; Mohammed El Amine Khelef (Техника и технология пищевых производств)
The quality of food products depends not only on the technological parameters of production process, but also on storage conditions. Smart packaging controls storage conditions and tracks violations. The research objective was to review the use of sensors in food storage. The study featured publically available information on sensor-equipped smart food packaging. The information was obtained from open sources published in 2016–2021. The paper describes biosensors, chemical sensors, and indicators that determine some of the characteristics of food products and provide information to the producer, retailer, and consumer. Indicators proved to be the most promising type of sensors used in smart packaging. This type of sensor indicates the presence and concentration of various analytes through color change. The best indicators are those based on radio frequency (RFID), poison identifiers, compaction/leaks indicators, indicators of freshness/ripeness, etc. All the considered indicators visualize their data by changing color, which makes it possible to assess the quality of food products on the market. Sensor-based smart packaging is a promising direction in food industry because they make it possible to monitor and control product quality. Smart packaging allows consumers to check the freshness of products by themselves.